PREDIKSI 3D-MOLEKULAR AKTIVITAS TURUNAN SENYAWA POLIHIDROKSI ZERUMBON TERHADAP GLIKOGEN SINTASE KINASE-3 BETA (GSK-3) MENGGUNAKAN DOCK6 - Broto Santoso; Dedi Hanwar; Andi Suhendi (Universitas Muhammadiyah Semarang, 2015)
Insulin resistance causes 90% of type 2 diabetes mellitus (DM) cases and this is due to an increase in the activity of glycogen synthase kinase-3 (GSK-3). Dephosphorylation and activation of glycogen synthase prevent type 2 diabetes by inhibiting the work of GSK-3 beta isoform primarily. The study was done in unix (mac and linux) operating system with the sequence of steps were optimization of geometry of ligand, ligand and protein preparation, validation of docking methods, molecular docking and analysis, and 3D modeling of ligand-protein interactions. Optimization of target ligand geometry using Gaussian showed that molecular docking score increased 62.5% compared with geometry optimization using MarvinSpace. Polyhydroxy compound zerumbon derivats: ZER04, ZER05 and ZER06 potential to be tested further in the laboratory as an anti- type 2 diabetes both in vitro and in vivo. This is based on the ability of the compounds in term of molecular interactions that better than the native ligand of target protein 4PTE, 4AFJ, 3ZRK, 3GB2, 3DU8 and 1Q3W (60% of the total protein targets tested) as an inhibitor of glycogen synthase kinase- 3 types of beta (GSK-3b).Keywords: polyhydroxyzerumbone, glycogen synthase kinase-3 beta, docking molecular, DOCK6